Investigating The Effect Of Sublingual Melatonin On The Rate Of Using Opioids In Laparotomy Patients Admitted To ICU (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Melatonin has sleep-inducing, analgesic, anti-inflammatory, and antioxidant properties, making it an appropriate supplement for managing pain in patients admitted to the intensive care unit (ICU). The present study aims to investigate the effect of sublingual melatonin on the rate of using opioids in laparotomy patients admitted to the ICU.Methods: This double-blinded randomized clinical trial was conducted on midline laparotomy patients hospitalized in the ICU of Imam Khomeini Hospital, Ahvaz in 2022. Fifty-five patients were randomly assigned to two groups, including one test group that received 5 mg of melatonin (n=27) for 3 consecutive nights and one placebo group (n=28). The rate of used opioids, pain intensity by visual analog scale (VAS), hemodynamic parameters, side effects, and duration of hospitalization in ICU were compared in two groups.Results: The rate of using opioids on the second day (81.5% vs. 100%; P=0.017) and the third day of hospitalization (55.6% vs. 82.1%; P=0.033) in the melatonin group was significantly lower than the control group. On the third day of hospitalization, the rate of using opioids (P=0.047) and the mean pain score (P=0.030) were significantly lower in the melatonin group compared to the control group. The mean duration of hospitalization in the ICU was not significant between the melatonin and placebo groups (P=0.428). Patients of the melatonin group experienced insignificantly less nausea and vomiting (18.5% vs. 35.7%) and hypotension (55.6% vs. 64.3%) compared to the placebo group.Conclusion: The present study revealed that the rate of using opioids and pain intensity was significantly lower in the melatonin group compared to the control group. Nocturnal melatonin supplementation can be recommended for managing pain in ICU patients and reducing the need for opioids and their side effects.